2021
DOI: 10.5114/jcb.2021.103590
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and evaluation of multi-channel cylinder applicator with 3D printing technology

Abstract: Purpose: This study was designed to assess dosimetric characteristics of 3D-printed personalized multi-channel cylinder applicator (MCCA). Material and methods: UnionTech RS Pro 600 (UnionTech, Inc., Shanghai, China) 3D printer was used for manufacturing MCCA. The geometry of MCCA was designed with Fusion 360 v.2.0.5827 (Autodesk, Inc.) software. The designed file was exported to Meshmixer v.3.5 (Autodesk, Inc.) to create three-dimensional model in stereolithography (STL) file format, which is the common file … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…The history of BT has been constantly accompanied by technological developments, and further advances are expected in the future in imaging, dose calculation algorithms, physical and biological dose optimization, new applicators, electromagnetic tracking, 3D printing and new isotopes [87][88][89]. We firmly believe that image-guided BT, supported by inverse dose planning, will compete successfully with high-tech EBRT in the coming times, and we sincerely hope that BT will survive for a long time to come, and serve as a valuable modality for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The history of BT has been constantly accompanied by technological developments, and further advances are expected in the future in imaging, dose calculation algorithms, physical and biological dose optimization, new applicators, electromagnetic tracking, 3D printing and new isotopes [87][88][89]. We firmly believe that image-guided BT, supported by inverse dose planning, will compete successfully with high-tech EBRT in the coming times, and we sincerely hope that BT will survive for a long time to come, and serve as a valuable modality for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Title and abstract screening was performed by the reviewers leaving 120 studies for assessment of full text for eligibility. Eighty-eight studies were excluded for the following reasons: models were not patient speci c (52), articles were duplicates (17), not the correct patient population (8), models were not printed (7), not in English (2), non-human models (1), and/or could not be accessed (1). In total 32 studies were included for review.…”
Section: Study Selectionmentioning
confidence: 99%
“…13 Our scoping review has highlighted that patient speci c 3D printed brachytherapy devices have been the most commonly studied individualized 3D printed model in gynecology in the literature to date. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The 3D printed models produced and studied were mainly personalized vaginal brachytherapy cylinder applicators and or interstitial brachytherapy needle templates in a population of patients with gynecologic malignanies including primary vaginal cancer, locally advanced or recurrent cervical or endometrial cancer. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In addition, some studies created 3D printed devices that could be personalized and used in combination with standardized applicators or templates.…”
Section: Medical Devicesmentioning
confidence: 99%
“…Preplanning is always essential and crucial to obtain a personalized 3D guidance template that can achieve the geometric description of inserted needles as well as the anticipated dose distribution in the target volume and OARs. 16,17 Huang et al 18 designed individual printed templates based on preplanning data that included 125 I seed locations and needle pathways for low-dose-rate radiation in patients with head and neck cancers. Sethi et al 19 inversely designed and printed 3D cylindrical templates through a preplanning process used for the pure interstitial therapy of two patients with vaginal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…investigated the use of a 3D‐printed template for the treatment of two patients at stage IVA with pure interstitial needles and found that the 3D‐printed template was efficient and potentially valuable for use in clinical practice. Preplanning is always essential and crucial to obtain a personalized 3D guidance template that can achieve the geometric description of inserted needles as well as the anticipated dose distribution in the target volume and OARs 16,17 . Huang et al 18 .…”
Section: Introductionmentioning
confidence: 99%